Bibliometric Analysis: Trends in Sharia Cooperatives Period 2008-2023 - Sofiatul Aini; Muh. Salahudin; Sobihatun Sobihatun (STKIP Taman Siswa Bima, 2025)
Sharia cooperatives are a business model that combines existing cooperative principles with sharia principles in economic activities. Sharia cooperatives have significant potential in promoting financial inclusion, poverty alleviation, and sustainable economic development. This research aims to analyze the trends and developments of sharia cooperatives during the period 2008-2023 published in Scopus data. A total of documents were found in the Scopus database to be used as research samples. The method used in this research is bibliometric analysis using VOSviewer as the analytical tool to determine the number of publications, the most productive authors, the most contributing institutions, and the most frequently used keywords in related publications. From the results obtained, the data shows that the research started from 2008 to 2023 and the data indexed in Scopus amounts to 374. The implications and contributions of this research are the mapping of research topics surrounding the Trends of Sharia Cooperatives from 2008 to 2023, both those frequently and rarely studied by researchers, so that other researchers can identify gaps in research on this topic.